The influence of variations in starter concentration Lactobacillus plantarum AS4 indigenous from human breast milk to the characteristics of fermented milk - Nosa Septiana Anindita; Annisa Khumaira (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
The fermentation of milk by Lactobacillus plantarum AS4 can be classified as a functional or nutraceutical food. Lactobacillus plantarum AS4 is a group of Lactic Acid Bacteria (LAB) isolated from human breast milk, which has the ability as a probiotic in vitro. This research aimed to determine the effect of Lactobacillus plantarum AS4 starter concentration on the characteristics of fermented milk produced. Variations concentration starter used were 0, 2, 4, 6, and 8% with an incubation temperature of 37 °C for 24 hours. Fermentation parameters collected were probiotic viability, total bacteria, titrable acidity, lactose, protein, and fat content. The results showed that variations in concentration starter Lactobacillus plantarum strain AS4 significantly affected the characteristics of fermented milk based on the parameters collected. The viability of fermented milk probiotics increased in milk treated with an 8% starter concentration variation (9.91 ±0.02 log CFU/mL) and total bacteria (8.84 ±0.07 log CFU/mL) in the fermented milk product. The levels of lactic acid (1.66 ±0.06%) and protein (4.32±0.03%) were also increased in fermented milk products with a starter variation of 8%. Significantly, fermented milk products with concentrations starter 8% decreased the pH value (4.10 ±0.01), lactose content (2.33±0.01%), and fat content (2.30±0.05%).